ANALISIS KEMAMPUAN KONEKSI MATEMATIS SISWA MTS NEGERI DI BANDUNG BARAT PADA MATERI SEGIEMPAT DAN SEGITIGA - Siti Nuraidah; Fauziah Siti Dewi Sarifah; Marchasan Lexbin Elvi Judah Riajanto; Rippi Maya (IKIP Siliwangi, 2018)
This research describes students mathematical connection ability in solving mathematical connection problems in a rectangular and triangular material. The research subjects were 30 students of class IX in one of MTs Negeri in West Bandung. Instruments in this research is a matter of test description of the ability of mathematical connection. Based on the result of mathematical connection ability test taken by 6 students from 30 students, that is 2 students with the high test result, 2 students with the medium test result, and 2 students with the low test result. From the research, it was found that: 1) students with high mathematical connection test result can solve the problem with indicator relation with other subjects and relation with daily life. 2) students with moderate test result can complete test question with indicator relationship with another subject. 3) students with low test result cannot solve all problems of mathematical connection ability. Based on the result of this study can be concluded that the mathematical connection ability of the class IX students in one MTs Negeri in West Bandung is still low.